The aims of the primary health care reforms in Finland between 1993-2015: a systematic review - Malinen, Sanna (Department of Public Health and Family Medicine, 2018)
Aims: Empirical research has proven that a strong primary health care (PHC) system produces better health outcomes and therefore, PHC is an important part of a country's health system. This systematic review focuses on the intended aims and targets of PHC reforms conducted in Finland from 1993 onwards. It describes the challenges that the Finnish PHC system has faced, comparing the objectives and the problem with other similar countries, providing lessons from the Finnish experiences for other countries. Methods: A Campbell-styled systematic review was conducted. Databases including Ebsco, Pubmed/MEDLINE, Scopus, Google Scholar and a Finnish health science database Medic were searched. The keywords and MeSH Terms for the review included terms relating to 'health systems', 'primary care', 'reform', and 'Finland' (see Appendix B). English terms were used when using Medline, Scopus and EBSCO, and both Finnish and English terms were used when using Medic. Reference lists of included papers were also searched. Data was extracted and analysed by utilising thematic analysis. Results: 13 relevant papers were found that dealt with PHC policies or reforms implemented in Finland between 1993 and 2015. The aims of the reforms were classified under five themes, which were developed based on a prior scoping review and then tested during data extraction. The themes were: efficient governance and financing, adequate and equitable access, improved quality, increased patient choice and cooperation and integration of services. Conclusions: A number of policies and reforms have been implemented which have directly or indirectly aimed to strengthen the Finnish PHC system. Some policies have intended to strengthen PHC overall while others have focused on only one aspect or challenge. There has recently been a strong tendency to re-centralise health services, and the importance of patient choice and service integration have become increasingly important. Integration and cooperation of different service providers is one of the newest solutions when finding ways to strengthen weak PHC systems. This study shows that in policy success context matters. PHC strengthening needs to be high on the political agenda, and enough resources are needed. This study showed that there have been few durable or sustainable solutions, and further research is needed especially from the overall health systems perspective.